Design and validation of a self-assessment scale of teaching digital competence and attitude towards educational innovation of in-service teachers - Dueñas Zorrilla, Mario; Tejada Fernández, José; Pozos Pérez, Katia Verónica (Revista Complutense de Educación, 2024)
Introduction. The aim of this work is to present the results of the process of construction and validation of the Self-assessment Scale of teachers’ digital competence (TDC) and attitude towards educational innovation of in-service teachers. For this, the dimensions and categories of the UNESCO ICT Competency Framework for Teachers (UNESCO, 2019) and the Common Framework for Teaching Digital Competence (INTEF, 2017) are considered as a basis. Method. The research is part of the instrumental studies. The reference population are secondary school teachers (two regions in the north of Chile). The piloting sample of the scale is made up of 200 people. For the validation, two procedures were used: content validity by expert judgment (10 international experts) and construct validity: exploratory factor analysis (EFA) and confirmatory factor analysis (AFC). Cronbach’s Alpha coefficient was used to establish reliability. Results. The content validity by expert judgment has made it possible to refine and adjust the initial global scale to 60 items, generating 3 subscales. The EFA establishes 3 major factors, verifying the correspondence with the three subscales of the questionnaire. The CFA indicates a good fit of the model with acceptable incremental fit indices (TLI, ILI, CFI) (0.90), as well as the RMSEA and SRMR residuals (0.06). Likewise, the parsimony-adjusted measures are high (greater than 0.07). Reliability is considered excellent (values greater than 0.90), both in the total scale and in the subscales studied. Conclusion. The self-assessment scale of digital teaching competence and attitude towards educational innovation, in light of the design and validation process developed, constitutes a robust, reliable and valid instrument for the evaluation of TDC and the attitude towards educational innovation.